Another Look at Rural-Nonrural Differences in Students' Educational Aspirations - Emil J. Haller; Sarah J. Virkler (Journal of Research in Rural Education, 1993)
Research suggests that rural youth have lower educational aspirations than their nonrural counterparts. This discrepancy has important implications for educational policy and for achieving equality of educational opportunity, and it has led some to propose that action is necessary to reduce the rural-nonrural variation. However,while the existence ofan aspirationdifference seemsclear, neither its magnitude nor the reason for its existence is similarly transparent. Before undertaking remedial actions, it is well to ascertain the nature of whatever discrepancy exists. That is the purposeof this paper. We find that the rural-nonrural difference in adolescents' educational aspirations is quite small, and that about half of this discrepancy can be attributed to the well-established divergence in socioeconomic status between rural and nonrural families. Our analyses also suggest that much-perhaps all-of the remaining difference derives from the slightly disparate occupational aspirations of rural and nonrural youth. We concludethat a goal to eliminate the small difference in rural-nonrural educational aspirationsis likely to beunachievable. The discrepancy'sroots lie in patterns offamily dynamics that are largelybeyond the reach of educators. If, however, theaim is simply to reduce the discrepancy, this might beaccomplished by raising the occupational aspirations of rural youth. However, that strategy has its own problems, most notably that it is likely to exacerbate the migration of talented young people from rural areas.